Effect of one session of aerobic exercise associated with abdominal laser therapy in lipolytic activity, lipid profile, and inflammatory markers - Barbosa, Patricia (2021)
Increased abdominal fat and sedentary lifestyles contribute to cardiovascular disease risk. The combination of exercise and low‐level laser therapy (LLLT) appears to be an innovative method to increase the lipolytic rate of abdominal adipocytes, in order to reduce abdominal fat.